Phosphatidic acid–regulated SOS2 controls sodium and potassium homeostasis in Arabidopsis under salt stress. (22nd February 2023) - Li, Jianfang; Shen, Like; Han, Xiuli; He, Gefeng; Fan, Wenxia; Li, Yu; Yang, Shiping; Zhang, Ziding; Yang, Yongqing; Jin, Weiwei; Wang, Yi; Zhang, Wenhua; et al.
Abstract: The maintenance of sodium/potassium (Na + /K + ) homeostasis in plant cells is essential for salt tolerance. Plants export excess Na + out of cells mainly through the Salt Overly Sensitive (SOS) pathway, activated by a calcium signal; however, it is unknown whether other signals regulate the SOS pathway and how K + uptake is regulated under salt stress. Phosphatidic acid (PA) is emerging as a lipid signaling molecule that modulates cellular processes in development and the response to stimuli. Here, we show that PA binds to the residue Lys57 in SOS2, a core member of the SOS pathway, under salt stress, promoting the activity and plasma membrane localization of SOS2, which activates the Na + /H + antiporter SOS1 to promote the Na + efflux. In addition, we reveal that PA promotes the phosphorylation of SOS3‐like calcium‐binding protein 8 (SCaBP8) by SOS2 under salt stress, which attenuates the SCaBP8‐mediated inhibition of Arabidopsis K + transporter 1 (AKT1), an inward‐rectifying K + channel. These findings suggest that PA regulates the SOS pathway and AKT1 activity under salt stress, promoting Na + efflux and K + influx to maintain Na + /K + homeostasis. Synopsis: The maintenance of Na + /K + homeostasis in plant cells is essential for salt tolerance. Here, the lipid signaling molecule phosphatidic acid (PA) is shown to determine the Na + /K + homeostasis under salt stress via SOS2 protein kinase‐dependent activation of Na + efflux via SOS1 and AKT1‐mediated K + influx. PA promotes the kinase activity and plasma membrane localization of SOS2 under salt stress. The residue Lys57 is critical for the PA‐mediated regulation of SOS2. The PA–SOS2 module activates the Na + /H + antiporter SOS1 to promote Na + efflux. The PA–SOS2 interaction also relieves the SCaBP8‐mediated inhibition of the inward K + channel AKT1 to promote K + uptake. Abstract : Increased membrane concentration of phosphatidic acid under salt stress protects plant cells by triggering the release of Na + and the uptake of K + .